Peranan Pemimpin Informal dalam Meningkatkan Partisipasi Masyarakat dalam Pembangunan di Desa Malola - Liow, Michael Rojer; Laloma, Alden; Pesoth, Welly (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Informal leaders are legitimate is not the leader/legality in Government, but theinformal leaders are part of the villagers whose role is crucial in giving influence to the residentsof the village. the role of informal leaders does not appear, this is because the formal leader ofthe village head is not too empowering the role of informal leadership. the purpose of thisresearch is to know the role of the Informal Leader in improving community participation indevelopment in the village Research methods used in this study is a qualitative method ofanalysis is the efforts made by way of working with data, organizing data, sifting through datainto units that can be managed, menyintesiskan data, search for and find patterns, find what isimportant and what is learned, and decide what can be told to others.The results of this research show that the informal leader's role in improving publicparticipation is very important amongst the people, but not too effective in terms of informingand invites the public to take part in development activities to increase the participation ofcommunity development need for sinerginitas between formal and informal leaders leadersKeword: Informal leaders, community participation in development